IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DALAM UPAYA MENUMBUHKAN MINAT BACA SISWA KELAS III DI SDN BONDONGAN, KOTA BOGOR - Dwi Julianti Saputri; Muhammad Juni Saputra; Nurlinda Safitri; Nurul Edriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the School Literacy Movement (GLS) Program in increasing the reading interest of grade III students at SDN Bondongan, Bogor City. The method used was descriptive qualitative with data collection techniques through observation, interviews and documentation. The results showed that the literacy program was implemented through mass literacy activities (LIMAS), reading habituation before learning, integration of literacy in subjects, and involvement of literacy ambassadors. Supporting factors for the success of the program include the commitment of principals and teachers, the availability of facilities such as reading corners and libraries, parental support and cooperation with mobile libraries. Constraints include the limited variety of age-appropriate reading materials, uneven teacher involvement, lack of literacy training and limited time and student motivation. Nevertheless, the positive experiences students had in reading activities, such as reading in the field or in a comfortable reading corner, were factors that triggered the growth of interest in reading. This study concludes that the implementation of GLS at SDN Bondongan has a positive impact on students' reading interest, but still requires strengthening in terms of teacher training, provision of varied reading materials, and comprehensive involvement strategies.